the INFLUENCE OF CIRCUIT TRAINING ON VO2MAX PERSERU FC FOOTBALL PLAYER RAMBAH UTAMA: PENGARUH LATIHAN CIRCUIT TRAINNING TERHADAP VO2MAX PEMAIN SEPAK BOLA PERSERU FC RAMBAH UTAMA - Rudi, Rudi Hartono; Manurizal, Lolia; Putra, Riwaldi (Journal Of Sport Education and Training, 2024)
This research started with observations of researchers in the field who saw the low VO2MAX ability of PERSERU FC Rambah Utama football players. For this reason, this study aimed to determine the influence of CIRCUIT TRAINING as an independent variable (X) on VO2MAX as the dependent variable (Y). This study used an experimental method with a One-Group Pretest-Postest Design. The sampling technique used a total sampling sample so that the total sample consisted of 16 people who were male. The research design used the Pre-test and Post-test using the Circuit Training test instrument to determine the increase in VO2MAX of Perseru FC football players. Data analysis and research hypothesis testing used an independent t-test (t-test) analysis technique with a significant level of α = 0.05. The results showed that circuit training exercises increased the vo2max of PERSERU FC football players with an average score of 99.3 in the pre-test, increasing from 14.3 to 113.6 in the post-test. The statistical results showed that (tcalculate 121.18 > ttable 1.753). This study concluded that Circuit Training influences increasing the VO2MAX of PERSERU FC Rambah Utama Football Players. Keywords: Circuit Training & VO2MAX Increase